2015
DOI: 10.1111/hae.12726
|View full text |Cite
|
Sign up to set email alerts
|

Mode of delivery and cranial bleeding in newborns with haemophilia: a systematic review and meta‐analysis of the literature

Abstract: Cranial bleeding occurs with a significantly higher frequency in newborns with haemophilia compared to the general population. In newborns with haemophilia, delivery by a CS is associated with the lowest risk of ICH. AVD significantly increases the risk of ICH and should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 43 publications
(82 reference statements)
1
48
1
Order By: Relevance
“…The circumstances surrounding the delivery, whether some of the CS deliveries were unplanned and occurred following the onset of labour, were not known. Davies and Kadir [11] performed a meta-analysis of observational cohort studies and prospective imaging studies and reported that newborns with haemophilia were 44 times more likely to experience symptomatic ICH compared to the general population and the odds ratio of experiencing ICH were 4.4 (95% CI: 1.46–13.7, P = 0.008) following an assisted vaginal delivery and 0.34 (95% CI: 0.14–0.83, P = 0.018) following CS compared to vaginal delivery. This has implications especially in pregnant carriers where the avoidance of assisted deliveries is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…The circumstances surrounding the delivery, whether some of the CS deliveries were unplanned and occurred following the onset of labour, were not known. Davies and Kadir [11] performed a meta-analysis of observational cohort studies and prospective imaging studies and reported that newborns with haemophilia were 44 times more likely to experience symptomatic ICH compared to the general population and the odds ratio of experiencing ICH were 4.4 (95% CI: 1.46–13.7, P = 0.008) following an assisted vaginal delivery and 0.34 (95% CI: 0.14–0.83, P = 0.018) following CS compared to vaginal delivery. This has implications especially in pregnant carriers where the avoidance of assisted deliveries is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial haemorrhage has been estimated to occur in 3%‐4% of neonates with haemophilia and has been associated with trauma at delivery, leading to debate on the optimal mode of delivery . The incidence of ICH in older children with haemophilia has been estimated previously at 2.02‐7.96 per 1000 patient years, but is less well defined in the modern era where, at least in the developed world, prophylaxis commenced early in childhood is widespread and may offer protection against all types of bleeding .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 11% of obstetricians in a US survey preferred C/S over vaginal delivery in carriers. 24 Cranial ultrasounds should be performed in severe haemophilia especially for traumatic delivery. 22,23 Davis and Kadir reported that haemophilic neonates were 44-times more likely to experience ICH compared to the general population.…”
Section: Birth/neonatementioning
confidence: 99%